Fitness of Outer Membrane Vesicles From Komagataeibacter intermedius Is Altered Under the Impact of Simulated Mars-like Stressors Outside the International Space Station - Podolich, Olga; Kukharenko, Olga; Zaets, Iryna; Orlovska, Iryna; Palchykovska, Larysa; Zaika, Leonid; Sysoliatin, Serhii; Zubova, Ganna; Reva, Oleg; Galkin, Maxym; Horid’ko, Tetyana; Kosiakova, Halyna; et al. (Frontiers in Microbiology, 2020)
Outer-membrane vesicles (OMVs), produced by nonpathogenic Gram-negative bacteria, have potentially useful biotechnological applications in extraterrestrial extreme environments. However, their biological effects under the impact of various stressors have to be elucidated for safety reasons. In the spaceflight experiment, model biofilm kombucha microbial community samples, in which Komagataeibacter intermedius was a dominant community-member, were exposed under simulated Martian factors (i.e., pressure, atmosphere, UV-illumination) outside the International Space Station for 1.5 years. In this study, we have determined that OMVs from post-flight K. intermedius displayed changes in membrane composition, depending on the location of the samples and some other factors. Membrane lipids such as sterols, fatty acids (FAs) and phospholipids were modulated under the Mars-like stressors, and saturated FAs, as well as both short-chain saturated and trans FAs, appeared in the membranes of OMVs shed by both post-UV-illuminated and “dark” bacteria. The relative content of zwitterionic and anionic phospholipids changed, producing a change in surface properties of outer membranes, thereby resulting in a loss of interaction capability with polynucleotides. The changed composition of membranes promoted a bigger OMV size, which correlated with changes of OMV fitness. Biochemical characterization of the membrane-associated enzymes revealed an increase in their activity (DNAse, dehydrogenase) compared to wild type. Other functional membrane-associated capabilities of OMVs (e.g., proton accumulation, interaction with linear DNA or synaptosomes) were also altered after exposure to the spaceflight stressors. Despite alterations in membranes, vesicles did not acquire endo-, cyto-, and neurotoxicity. Altogether, our results show that OMVs, originating from rationally selected nonpathogenic Gram-negative bacteria, can be considered as candidates in the design of postbiotics or edible mucosal vaccines for in situ production in extreme environment. Furthermore, these OMVs could also be used as promising delivery vectors for applications in Astromedicine.